Dziecięce rozumienie świata – w poszukiwaniu uzasadnień postępowania badawczego - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
Reflecting on the understanding of the world from the perspective of children is significant for several reasons. First, it allows us to examine the kind of thinking and actions of children which is of an interpretative nature: it reveals not only the child’s personal knowledge, but above all, the ways of understanding, categorising and evaluating an ambiguous and often conflicted reality. It also provides an opportunity to reconstruct the cognitive skills manifested in the verbal and non-verbal reactions of children put in front of an organised problematic situation. In view of such a conclusion, it is worth taking the time to analyse the complex problem: how children perceive the world and how to reconstruct in practice children’s processes associated with understanding, categorising, and evaluating the world.